Position statement of the HAE Section of the Polish Society of Allergology on the management of hereditary angioedema due to C1 inhibitor deficiency: 2025 update. Part II: treatment, monitoring, perioperative management, and the particular aspects of care for women and children - Porębski, Grzegorz; Kucharczyk, Aleksandra; Matuszewski, Tomasz; Danielewicz, Hanna; Gocki, Jacek; Grzela, Katarzyna; Juchacz, Aldona; Kurowski, Marcin; Kuziemski, Krzysztof; Łukaszyk, Mateusz; Sokołowska, Małgorzata; Stobiecki, Marcin; et al. (Alergologia Polska - Polish Journal of Allergology, 2025)
The second part of the updated guidelines focuses on the treatment of hereditary angioedema with C1 inhibitor deficiency (HAE-C1INH), as well as the specific clinical presentation and management of HAE in special populations, particularly women and children. This section also emphasizes the importance of patient education and appropriate disease monitoring throughout the course of therapy. One of the most significant developments in recent years has been the evolution of long-term prophylaxis (LTP). Several new agents have been approved for use, showing high efficacy in reducing the frequency and severity of attacks, while also contributing to the normalization of patients’ daily functioning and quality of life – all with a favorable safety profile. As a result, a growing number of patients are being successfully managed with LTP. Furthermore, this section elaborates on recommendations for short-term prophylaxis and perioperative management. Since the effectiveness and safety of therapy are closely linked to patient adherence, the guidelines also address home treatment protocols, structured monitoring strategies, and the organization of comprehensive patient care in Poland.